PERLINDUNGAN HUKUM BAGI KREDITOR YANG BERITIKAD BAIK AKIBAT PEMBATALAN HAK TANGGUNGAN - Lilawati Ginting (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Security rights aims for giving protection and legal certainty for stakeholders, which one it is dependent creditor rights holders, but in practice this goal still cannot fully carried out, due to ongoing security rights can still be canceled court. Debitors must still be my response if the object binding guarantee with the court canceled encumbrance, such as spending manifestly been issued by the creditors, and for loss of expected profit from lending. Other efforts to do creditor to restore the rights of Its preferred to debtors, namely by requiring the debtor to replace a security object that has been canceled court with other objects which have a face value equal, and then do the loading objects according to new guarantee, such as in the form of a security interest, fiduciary, mortgages or liens.